2011
DOI: 10.2217/pgs.11.109
|View full text |Cite
|
Sign up to set email alerts
|

Association Between DNA-repair Polymorphisms and Survival in Pancreatic Cancer Patients Treated with Combination Chemotherapy

Abstract: Polymorphisms of DNA-repair genes appear to be candidate biomarkers of primary resistance to gemcitabine/cisplatin-based polychemotherapeutic regimens. The relatively small sample size, coupled with the retrospective and exploratory design of the present study, imply that these results should be considered as hypothesis generators, and should be further evaluated in larger and adequately designed retrospective/prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
6
32
0
1
Order By: Relevance
“…The findings of previous studies in NSCLC and pancreatic cancer patients were similar to ours with respect to XPD codon 751 polymorphisms (53,55,56). The negative results might be explained by the sample size that is not large enough to detect a small effect from SNPs of low penetrance, alternatively, due to exclusion of other DNA repair genes that might synergistically act with the analyzed genes in normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of previous studies in NSCLC and pancreatic cancer patients were similar to ours with respect to XPD codon 751 polymorphisms (53,55,56). The negative results might be explained by the sample size that is not large enough to detect a small effect from SNPs of low penetrance, alternatively, due to exclusion of other DNA repair genes that might synergistically act with the analyzed genes in normal tissues.…”
Section: Discussionsupporting
confidence: 89%
“…312 (Asp to Asn) and 751 (Lys to Gln) were the main two polymorphisms that induce amino acid changes in the proteins (Shen et al, 1998). The associations of the Lys751Gln polymorphism in XPD gene with the prognosis of various types of cancer have been widely reported in cancer epidemiologic studies, such as colorectal cancer, advanced lung cancer, oral cancer and pancreatic cancer (Giovannetti et al, 2011;Biason et al, 2012;Chen et al, 2012;Mahimkar et al, 2012;Slyskova et al, 2012). In our study, we have found polymorphism in XPD Lys751Gln is related to the prognosis of HCC, which has provided evidence that the XPD protein influences the overall survival of HCC through NER pathway.…”
Section: Discussionsupporting
confidence: 69%
“…XRCC1 gene polymorphisms are reported to be correlated with the treatment outcome of cisplatin-based chemotherapy in several kinds of cancers, such as gastric cancer, colorectal cancer, nasopharyngeal cancer, ovarian cancer, pancreatic cancer, and esophageal cancer (Warnecke-Eberz et al, 2009;Giovannetti et al, 2011;Miao et al, 2012;Chen et al, 2013;Cao et al, 2014;Wu et al, 2014). Currently, several studies have reported the association between XRCC1 genetic polymorphisms and treatment outcome of advanced NSCLC (Yuan et al, 2006;Wang et al, 2004Wang et al, , 2008Sun et al, 2009;Li et al, 2011;Ke et al, 2012;Han et al, 2015).…”
Section: Discussionmentioning
confidence: 99%